2023
DOI: 10.1038/s41598-023-44914-w
|View full text |Cite
|
Sign up to set email alerts
|

Altered reward processing in patients with lifelong premature ejaculation

Yansong Li,
Xiaojun Li,
Zixiang Wang
et al.

Abstract: Given that sexual behavior is usually pleasurable and highly rewarding, it is surprising that there is as yet no known research to empirically assess how premature ejaculation (PE) patients respond to the rewarding aspect of sexual behavior. This study was designed to address this issue by evaluating how these men respond to the anticipation and hedonic experience of sexual rewards in comparison to non-sexual rewards. Thirty lifelong PE patients and thirty healthy controls (HCs) performed the incentive delay t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Likewise, a structural MRI study demonstrated increased structural covariance between the striatum and thalamus, which showed potential higher sensitivity to sexual stimulation in PE patients (Wu et al., 2022). A recent study observing the response of PE patients to both sexual and nonsexual rewards suggested enhanced incentive motivation and hedonic impact of sexual stimuli, which highlighted an allostatic shift in the reward processing pathways of PE patients (Li, Wang, et al., 2023). Based on our findings, the higher functional connectivity and increased global integration of information might again reinforce the abnormalities of PE patients in sensory and emotional processing, controlling sexual inhibition, and reacting to reward‐related information (Wu et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a structural MRI study demonstrated increased structural covariance between the striatum and thalamus, which showed potential higher sensitivity to sexual stimulation in PE patients (Wu et al., 2022). A recent study observing the response of PE patients to both sexual and nonsexual rewards suggested enhanced incentive motivation and hedonic impact of sexual stimuli, which highlighted an allostatic shift in the reward processing pathways of PE patients (Li, Wang, et al., 2023). Based on our findings, the higher functional connectivity and increased global integration of information might again reinforce the abnormalities of PE patients in sensory and emotional processing, controlling sexual inhibition, and reacting to reward‐related information (Wu et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…PE is characterized by a man's inability to maintain ejaculatory control as desired, resulting in a short intravaginal ejaculation latency time (IELT), such as ejaculating within one minute of penetration ( Althof et al, 2014 ), which in turn leads to sexual distress as well as diminished self-esteem and self-confidence ( Rowland et al, 2007 ; Symonds et al, 2003 ) and heightened levels of anxiety and depression ( Ermeç et al, 2022 ; Porst et al, 2007 ), increased interpersonal difficulties ( Giuliano et al, 2008 ; Patrick et al, 2005 ), and an altered rewarding processing (Y. Li et al, 2023 ). Furthermore, men suffering from PE symptoms have female sexual partners with reduced relationship and sexual satisfaction, elevating the risk of sexual dysfunction ( Jern et al, 2020 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%